2021
DOI: 10.3390/ani11061585
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Beta-Lactam-Resistant Escherichia coli and Toxigenic Clostridioides difficile Strains in Wild Boars Foraging in an Anthropization Gradient

Abstract: Disease transmission among wild boars, domestic animals and humans is a public health concern, especially in areas with high wild boar densities. In this study, fecal samples of wild boars (n = 200) from different locations of the Metropolitan Area of Barcelona were analyzed by PCR to explore the frequency of β-lactamases and extended cephalosporin and carbapenem resistance genes (ESBLs) in Escherichia coli strains and the presence of toxigenic Clostridioides difficile. The prevalence of genes conferring resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
(50 reference statements)
3
17
1
Order By: Relevance
“…Regarding the bacterial isolates, a total of 90 bacterial isolates were identified from those 67 analysed animals, and AMR genes were detected in 52 isolates. Thus, in line with other studies [28,29], we observed that some of the AMRB did not have any of the AMR genes. This could be explained by the possible existence of other mechanisms of resistance such as chromosomal mechanisms that were not included as a target of this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the bacterial isolates, a total of 90 bacterial isolates were identified from those 67 analysed animals, and AMR genes were detected in 52 isolates. Thus, in line with other studies [28,29], we observed that some of the AMRB did not have any of the AMR genes. This could be explained by the possible existence of other mechanisms of resistance such as chromosomal mechanisms that were not included as a target of this study.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of β-lactamase resistance genes has been historically analysed using E. coli as a marker in livestock [34] and wildlife [35][36][37]. Regarding wildlife, the presence of ESBL genes has been reported principally in wild birds [38][39][40], but also in other species such as bats [41], wild boars [29], and fish [42]. The most commonly detected ESBL genes are CTX-M-1, CTX-M-14, and CTX-M-15, which are also found frequently in hospital settings, suggesting a relationship between bacteria from wildlife and health-care facilities [33].…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic resistance to cephalosporins has been investigated worldwide and the host taxa that carry cephalosporinases in Europe include birds, mammals, reptiles, fish, and mollusks [ 8 ]. Considering wild mammals, the bla SHV has been reported in Gram-negative bacteria with reduced susceptibility to third-generation cephalosporins from wild boars, European hedgehogs, beech marten, and European badgers in Spain and Italy [ 42 , 43 , 44 ]. The blaTEM gene was reported in resistant E. coli from wild boars in Portugal, Poland, and Spain and it was considered by some authors the most frequent gene conferring resistance to β-lactams [ 43 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering wild mammals, the bla SHV has been reported in Gram-negative bacteria with reduced susceptibility to third-generation cephalosporins from wild boars, European hedgehogs, beech marten, and European badgers in Spain and Italy [ 42 , 43 , 44 ]. The blaTEM gene was reported in resistant E. coli from wild boars in Portugal, Poland, and Spain and it was considered by some authors the most frequent gene conferring resistance to β-lactams [ 43 , 45 , 46 ]. Otherwise, in Italy, a low prevalence of bla TEM was reported in resistant isolates from wild boars collected in Emilia Romagna and Lombardy regions [ 18 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation